Preliminary validation of a Urinary Symptom Questionnaire for individuals with Neuropathic Bladder using Intermittent Catheterization (USQNB-IC): A patient-centered patient reported outcome. - Rochelle E Tractenberg; Suzanne L Groah; Amanda K Rounds; Inger H Ljungberg; Manon M Schladen (PLoS ONE, 2018)
BACKGROUND:We developed a Urinary Symptom Questionnaire for individuals with neurogenic bladder due to spinal cord injury (SCI) and spina bifida (SB) who manage their bladders with intermittent catheterization, the USQNB-IC. This project followed an approach to patient-centered patient reported outcomes development that we created and published in 2017, specifically to ensure the primacy of the patient's perspective and experience. PARTICIPANTS:Two sets of responses were collected from individuals with neurogenic bladder due to either SCI (n = 336) and SB (patients, n = 179; and caregivers of patients with NB, n = 66), and three sets of "controls", individuals with neurogenic bladder who do not have a history of UTIs (n = 49) individuals with chronic mobility impairments (neither SCI nor SB) and without neurogenic bladder (n = 46), and those with no mobility impairment, no neurogenic bladder, and no history of UTIs (n = 64). METHOD:Data were collected from all respondents to estimate these psychometric or measurement domains characterizing a health related PRO: Reliability (minimization of measurement error; internal consistency or interrelatedness of the items; and maximization of variability that is due to "true" difference between levels of the symptoms across patients), and validity (content, reflection of the construct to be measured; face, recognizability of the contents as representing the construct to be measured; structural, the extent to which the instrument captures recognizable dimensions of the construct to be measured; and criterion, association with a gold standard). RESULTS:Evidence from these five groups of respondents suggest the instrument has face, content, criterion, convergent, and divergent validity, as well as reliability. The items were all more descriptive of our patient (focus) groups and were only weakly endorsed by the control groups. CONCLUSIONS:The instrument is unique in its emphasis on, and origination from, the lived experiences of patients with neurogenic bladder who use intermittent catheterization; this preliminary psychometric evidence suggests the instrument could be useful for research and in the clinic. These results justify further development of the instrument, including formal exploration of the scoring and estimation of responsivity of these items to clinical interventions as well as patient-directed self care.